The Contribution Of Vet To Twin Transition: Quality, Competence And Participatory Improvement Through Peer Review - Boerchi, Diego; Evangelista, Laura; Fonzo, Concetta (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
This contribution presents peer review as a key strategy for transforming quality assurance of Vocational Education and Training (VET) systems, particularly in the context of the green and digital transitions. Grounded in the EQAVET framework, Peer Review is framed not as a bureaucratic exercise but as a participatory and competence-driven process. The article describes an in-progress study mapping the roles and competences required to implement peer review effectively. Using task and job analysis combined with semi-structured interviews and the Critical Incident Technique, the study identifies six essential roles, including emerging ones such as Green and Digital Managers. These roles contribute to a sustainable culture of quality and help align institutional practices with EU priorities. The paper emphasizes the strategic importance of investing in human capital to support systemic change and ensure VET’s proactive contribution to Europe’s twin transition.